The defintions of information and security; history of information security development - Ibrahimova, Aytakin Nazim (Vilnius University Open Series, 2020)
Taking into consideration its historical evolvement, it is evident that information security is not a new concept. Starting from the very moment of writing down the information, it presents by itself a data that can be protected, stolen, or destroyed. Throughout the whole history, without even perceiving it people had to take steps to guarantee the security of important information that they have been able to maintain. The concept of information security is quite dynamic. A behaviour that is generally accepted today can be a peril to an entity that we will work with tomorrow. Developing technology brings along the continuous innovation. Everyone handles personal information when it comes to technology development or service provision. Besides already existing services, it includes banking and other activities. Therefore, we should bear in mind that personal security cannot be ensured without guaranteeing security within each organization.
Keywords: information; information security; data carriers; coverage area; information systems; information infrastructure; computer and network security; history of information security development